Innate Immune Tolerance in Microglia Does Not Impact on Central Nervous System Prion Disease - Pal, Reiss; Bradford, Barry M.; Mabbott, Neil A. (Frontiers in Cellular Neuroscience, 2022)
Prion diseases such as Creutzfeldt-Jakob disease in humans, bovine spongiform encephalopathy in cattle and scrapie in sheep, are infectious and chronic neurodegenerative diseases to which there are no cures. Infection with prions in the central nervous system (CNS) ultimately causes extensive neurodegeneration, and this is accompanied by prominent microglial and astrocytic activation in affected regions. The microglia are the CNS macrophages and help maintain neuronal homeostasis, clear dead or dying cells and provide defence against pathogens. The microglia also provide neuroprotection during CNS prion disease, but their pro-inflammatory activation may exacerbate the development of the neuropathology. Innate immune tolerance induced by consecutive systemic bacterial lipopolysaccharide (LPS) treatment can induce long-term epigenetic changes in the microglia in the brain that several months later can dampen their responsiveness to subsequent LPS-treatment and impede the development of neuritic damage in a transgenic mouse model of Alzheimer’s disease-like pathology. We therefore reasoned that innate immune tolerance in microglia might similarly impede the subsequent development of CNS prion disease. To test this hypothesis groups of mice were first infected with prions by intracerebral injection, and 35 days later given four consecutive systemic injections with LPS to induce innate immune tolerance. Our data show that consecutive systemic LPS treatment did not affect the subsequent development of CNS prion disease. Our data suggests innate immune tolerance in microglia does not influence the subsequent onset of prion disease-induced neuropathology in mice, despite previously published evidence of this effect in an Alzheimer’s disease mouse model.